Diagnosis of Cellulitis in Patients Infected with the Human Immunodeficiency Virus - Ireneo Diaz; Suresh Neelagaru; Lawrence Dall (Canadian Journal of Infectious Diseases)
A prospective microbiological evaluation of cellulitis in 22 patients infected with the human immunodeficiency virus was performed. Patients with helper lymphocyte counts of less than 200 cells/mm3 had a greater frequency of positive cultures. The most frequently isolated pathogens were Staphylococcus aureus and Streptococcus pyogenes, and initial antibiotic therapy should cover these Gram-positive cocci.